ORTHOGRAPHIC-PHONETIC INTERFACE: RECOGNITION OF SCHWA /Ə/ AT DIGRAPHIC WORD-FINAL POSITION - Dr. Shazia Kousar; Zain Khalid; Ali Hassan; Ayesha Fatima; Phool Sawera (International Journal of Contemporary Issues in Social Sciences, 2024)
This study embarks on investigating the complex interface between the phonological representation of the schwa /ə/ and its corresponding orthographic form at word final digraphic position. The researchers intend to expound the perception and recognition of vowel-letter harmony of /ə/ of English as L2 in Pakistani context. The students enrolled in BS English program at the department of English, University of Narowal, Pakistan, formed the cohort of the study for data collection. Quantitative analysis of the data revealed important insights. The participants correctly perceived and recognized 73% words with digraph or and 74% with digraph er. However, the percentage of correct perception and recognition of ar digraph o vowel sound was 61%. These findings provide important empirical evidence for examining sound-letter interfaces that particularly highlighting the complexity English vowel system particularly vowel sound. The findings of this study stand to enrich our understanding of the interplay between sound and script, contributing to linguistic knowledge, and offer insights for language pedagogy and language learning.